2021
DOI: 10.3390/ijms22116137
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Collagen Hydrolysates Ameliorate Furrowed and Parched Skin Caused by Photoaging in Hairless Mice

Abstract: Collagen hydrolysates have been suggested as a favorable antiaging modality in skin photoaged by persistent exposure to ultraviolet radiation (UV). The current study evaluated the beneficial effect of collagen hydrolysates (fsCH) extracted from Pangasius hypophthalmus fish skin on wrinkle formation and moisture preservation in dorsal skin of hairless mice challenged with UV-B. Inter-comparative experiments were conducted for anti-photoaging among fsCH, retinoic acid (RA), N-acetyl-D-glucosamine (NAG), and glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Reportedly, hyaluronic acid decreases due to ultraviolet irradiation and aging. 38,39 Therefore, this molecule is incorporated into various cosmetics as a countermeasure against age-related loss of skin moisture, loss of elasticity, and increase of wrinkles. Ceramide is responsible for the barrier function of the skin, and the amount of ceramide was reported to be decreased in the skin of atopic dermatitis patients with reduced skin moisture content and disruption of barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, hyaluronic acid decreases due to ultraviolet irradiation and aging. 38,39 Therefore, this molecule is incorporated into various cosmetics as a countermeasure against age-related loss of skin moisture, loss of elasticity, and increase of wrinkles. Ceramide is responsible for the barrier function of the skin, and the amount of ceramide was reported to be decreased in the skin of atopic dermatitis patients with reduced skin moisture content and disruption of barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, hyaluronic acid decreases due to ultraviolet irradiation and aging 38,39 . Therefore, this molecule is incorporated into various cosmetics as a countermeasure against age‐related loss of skin moisture, loss of elasticity, and increase of wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…The collagen hydrolysates fsCH were derived from fish skin gelatin, and digested with non-pathogenic Bacillus collagenase-type protease (Amicogen Inc., Jinju, Korea). The preparation and HPLC analysis of fsCH were as previously detailed [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study conducted inter-comparative experiments for anti-osteoporotic activity among fsCH, isoflavone, glycine–proline–hydroxyproline (GPH) tripeptide, and calcium lactate. In our previous study [ 34 ], the crude proteins formed ~97% in fsCH, and the contents of collagen tripeptides and GPH were 32.67 ± 0.22% and 3.22 ± 0.02%, respectively. GPH is considered to be a collagen-specific sequence, and is initially hydrolyzed to the dipeptide proline–hydroxyproline (PH) by the epithelium-bound aminopeptidase on the intestinal brush border membrane [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 95%
“…Increasing scientific evidence has shown that collagen hydrolysate from fish skin gelatin prevents wrinkle formation, melanogenesis, and skin dryness. We reported previously that collagen or collagen hydrolysate supplementation contributes to good skin health ( Kang et al, 2018 ; Lee et al, 2019 ; Kang et al, 2021 ; Park et al, 2021 ; Kim et al, 2022 ). Previous studies have reported that fish collagen peptide could weaken intestinal inflammation and treat diet-induced obesity and associated disorders ( Astre et al, 2018 ; Rahabi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%